The Role of Statutory Notes in Informing Market Players - Kerezsi, Dóra (International Journal of Engineering and Management Sciences, 2017)
The conduct of numerous economic operators is influenced by the globalization accelerated nowadays. In this connection, it can be certainly said that the globalization affects the accounting regulation as well. In our country, the business entities falling within the scope of the aforementioned regulation are subject to Act C of 2000 on Accounting, according to which the prepared reports shall provide the external and internal stakeholders with information ensuring a true and fair overall picture of the business entities’ property, financial and profitability situation as well as future plans. Over the recent years, the reason of changes in the Accounting Act was the harmonisation with other laws thus the main part of the change in year 2016 was the obligatory transposition of the Directive 2013/34/EU into the domestic law system as well as the completion of the previous deficiencies. These changes influence the system of accounting records that has been already established. In my treatise, I will highlight a part of the report i.e. the Notes providing text information in addition to the numerical data. Furthermore, the changes in Act of 2016 on Accounting will be presented with respect to the Notes.